Public health education initiatives for testicular torsion. Issue 6 (26th November 2020) - Green, Charles; Stubbs, Vicky; Green, James SA
Abstract : Preventable loss of an organ through lack of knowledge could be seen as shocking in the twenty‐first century. That is why a campaign to improve knowledge about and awareness of testicular torsion is underway.